(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
Through the analysis of various sources on the Argentine popular cult called "Difunta Correa" it seeks to recompose its political context, in the struggles between unitaries and federalists of the 19th century. I analyze the process of cultural interventions on this history, which is making women invisible in the popular mobilizations against the emergence of the state, at the same time that the order of the family institution is being perfected.